2017
DOI: 10.1007/s00011-017-1110-y
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 and phosphatases modulate COX-2 protein expression and TAU phosphorylation in cultured immortalized podocytes

Abstract: These data suggest TGF-β1 mediates its effect in podocyte through novel signaling mechanisms including phosphatases and TAU protein phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Podocyte injury is mostly associated with foot processes effacement leading to podocyte detachment or apoptosis. 7 In this study, we also found that ghrelin induced TAU phosphorylation. 44 Recently, we found that PGE2 can significantly modulate TAU protein phosphorylation.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Podocyte injury is mostly associated with foot processes effacement leading to podocyte detachment or apoptosis. 7 In this study, we also found that ghrelin induced TAU phosphorylation. 44 Recently, we found that PGE2 can significantly modulate TAU protein phosphorylation.…”
Section: Discussionsupporting
confidence: 67%
“…5 Finally, overexpression of COX predisposed to albuminuria and caused podocyte damage. 7,8 Also, stimulation of podocytes with PGE2 reduced AKT phosphorylation levels, a survival kinase that protects podocytes from cell death induced by advanced glycation end products. 7,8 Also, stimulation of podocytes with PGE2 reduced AKT phosphorylation levels, a survival kinase that protects podocytes from cell death induced by advanced glycation end products.…”
mentioning
confidence: 99%
See 3 more Smart Citations